Notes on Cobordism Theory - Stong, Robert E. (Princeton Legacy Library, 2016)
These notes contain the first complete treatment of cobordism, a topic that has become increasingly important in the past ten years. The subject is fully developed and the latest theories are treated.Originally published in 1968.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905